Delivering better policies through behavioural insights : new approaches. (OECD Publishing, 2019)
As behavioural insights (BI) become more widely used, countries are looking to expand the application of the methodology to new frontiers of policy making. This report tests behaviourally informed solutions to complex policy problems in the fields of competition, consumer protection, energy consumption and safety through a variety of theoretical and experimental approaches. The results give policy makers new ideas for tackling policy problems related to individual behaviour, as well as for changing the behaviour of organisations.